Physicochemical Properties and Malting Potential of New Canadian Hulless Barley Genotypes. (3rd April 2023) - Izydorczyk, Marta S.; Badea, Ana; Beattie, Aaron D.
Abstract: Interest in malting hulless barley (HB) is driven by its potential to produce very high levels of malt extract, but elevated levels of wort ß-glucan and insufficient levels of enzymes in hulless malt have prevented its widespread use. The objective of this study was to highlight the recent advancements in quality improvement of Canadian HB for malting purposes. Five advanced HB lines were evaluated for various barley and malt quality characteristics. All hulless lines exhibited lower grain hardness and slightly lower kernel weight and diameter compared to AAC Synergy (a popular two-rowed covered Canadian variety). The average total starch content of the hulless barley lines (64.2%) was significantly higher than AAC Synergy (59.9%) but slightly lower than that of CDC Clear (65.1%). Despite the low friability values, HB malts had a crumbly texture with good solubility and enzyme accessibility resulting in ample production of fermentable sugars. The average chain length of starch hydrolysis products in wort of new HB lines was similar to that of AAC Synergy, indicating sufficient enzyme activities and a highly effective hydrolysis. The fine-grind extract levels from hulless malt were on average 8% higher than from AAC Synergy, and several new HB lines exceeded the level of CDC Clear extract by 0.7–1.0%. Compared to CDC Clear, the new HB lines showed a significant reduction in concentration of wort ß-glucans. The concentration and the average degree of polymerization of arabinoxylo-oligosaccharides in wort of HB lines were generally higher than in wort of AAC Synergy, partly explaining the higher viscosity of HB worts. In general, the recently developed HB lines exhibited excellent malting potential with significant improvements in the levels of malt enzymes, concentration of free amino nitrogen compounds, and β-glucans in wort.